2004
DOI: 10.1016/s0749-8063(04)00599-7
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic treatment of 105 lateral meniscal cysts with 5-year average follow-up

Abstract: Level IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 0 publications
1
23
0
1
Order By: Relevance
“…We could not find a case in the literature of concomitant bucket-handle tear and meniscal cyst. Meniscal cysts accompany meniscal tears and the most common tear pattern is the horizontal cleavage tear8 which is in accordance with our case. Moreover, the displaced meniscal fragment is usually located into the notch and not onto the medial portion of the lateral compartment 6 9.…”
Section: Discussionsupporting
confidence: 92%
“…We could not find a case in the literature of concomitant bucket-handle tear and meniscal cyst. Meniscal cysts accompany meniscal tears and the most common tear pattern is the horizontal cleavage tear8 which is in accordance with our case. Moreover, the displaced meniscal fragment is usually located into the notch and not onto the medial portion of the lateral compartment 6 9.…”
Section: Discussionsupporting
confidence: 92%
“…It is generally accepted that parameniscal cysts in the knee are associated with meniscal tears [8][9][10][11][12] and paralabral cysts in the shoulder with labral tears [13]. Both require therapy, not only of the cysts, but also of the associated meniscal or labral abnormality in order to prevent recurrence of cyst formation [14].…”
Section: Discussionmentioning
confidence: 99%
“…11,12,39 Eleven studies reported data on the rate of cyst recurrence after pure arthroscopic decompression, which was calculated to be 37/445 (8.3%) (Table 4). 1,26,33,34,[40][41][42][43][44][45][46] Similarly, 3 studies were used to calculate a recurrence rate of 5/147 (3.4%) for arthroscopic excision (Table 4). 1,40,47 studies provided insight on the rates of recurrence after arthroscopy assisted percutaneous decompression, which was calculated to be 0/37 (0%) (Table 4).…”
Section: Rates Of Cyst Recurrencementioning
confidence: 99%